2015
DOI: 10.3329/jemc.v5i1.21492
|View full text |Cite
|
Sign up to set email alerts
|

Admission Serum Uric Acid Levels and In-Hospital Outcomes in Patients with Acute Coronary Syndrome

Abstract: Background: Uric acid is an independent risk factor for cardiovascular disease. Hospital admission for ischemic heart disease (IHD) is increasing rapidly in our country. Although studies were conducted abroad regarding association of serum uric acid with in-hospital outcomes in patients with acute coronary syndrome (ACS), no data is yet available to show the association in our country. Objective: The objective of this study was to assess the association of serum uric acid level on admission with in-hospital ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Similar finding was found by Dharma et al 13 Significant difference was observed by Bickel et al 19 and Omidver et al 14 Confounding variables such as hypertension, diabetes mellitus, smoking, dyslipidaemia and family history of IHD were not significant between high and normal serum uric acid level patients. Similar findings observed by Dharma et al 13 and Abdullah et al 24 Lim et al 25 found no significant relationship between hypertension and smoking with patients of CAD having high uric acid. Bae et al 26 showed no significant relationship between hypertension, diabetes mellitus, dyslipidaemia with patients of high serum uric acid having CAD.…”
Section: Results: 115 Patients Were Included In This Studysupporting
confidence: 81%
See 1 more Smart Citation
“…Similar finding was found by Dharma et al 13 Significant difference was observed by Bickel et al 19 and Omidver et al 14 Confounding variables such as hypertension, diabetes mellitus, smoking, dyslipidaemia and family history of IHD were not significant between high and normal serum uric acid level patients. Similar findings observed by Dharma et al 13 and Abdullah et al 24 Lim et al 25 found no significant relationship between hypertension and smoking with patients of CAD having high uric acid. Bae et al 26 showed no significant relationship between hypertension, diabetes mellitus, dyslipidaemia with patients of high serum uric acid having CAD.…”
Section: Results: 115 Patients Were Included In This Studysupporting
confidence: 81%
“…There was no significant difference of mean BMI between high and normal serum uric acid level patients. Omidvar et al 14 and Abdullah et al 24 found similar finding. Significant association between mean BMI and high uric acid observed by Bickel et al 19 and Timoteo et al 15 There was no significant difference of confounding variables between high and normal serum uric acid level patients.…”
Section: Results: 115 Patients Were Included In This Studymentioning
confidence: 56%
“…Lazzeri et al 28 studied 466 STEMI patients, and Car et al 29 assessed 621 AMI patients and showed in-hospital mortality was higher in patients with elevated uric acid. Death was not significant in hyperuricaemic patients as in normouricemic patients observed by Culleton et al 13 and Abdullah et al 27 Our study provided a significant association between high serum uric acid level on admission and poor in-hospital outcomes like acute LVF and death in AMI of hospitalized patients. The measurement of serum uric acid levels, an easily available, cheap biochemical tool, might be used as a valuable risk marker for detection and prevention of in-hospital outcomes in AMI patients.…”
Section: Discussionsupporting
confidence: 53%
“…Cardiogenic shock was not significantly higher in patients with higher serum uric acid levels than patients with normal uric acid levels. Abdullah et al 27 studied 93 ACS patients and found similar findings. Ndrepepa et al 23 and Chen et al 25 found a significant association between cardiogenic shock and high serum uric acid.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation